Review Rekam Medis Pasien Ruang Isolasi Covid-19 RSU Imelda Pekerja Indonesia Tahun 2020 - Mei Sryendang Sitorus; Esraida Simanjuntak; Valentina Valentina (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
Quantitative Analysis is a review of certain parts of the contents of medical records to find deficiencies, especially those related to the documenting of medical records. Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2). The purpose of this study is to find out the implementation of the Covid-19 Isolation Room Patient Medical Record Document Review at RSU Imelda Pekerja Indonesia in 2020. The population is all patients treated in the Covid-19 Isolation Room in 2020 as many as 182 people, the study sample is all patients treated in the Covid-19 Isolation Room in October as many as 48 people. The DRM review was conducted on four variables. From the results of the study obtained that the Review of Timeliness of appropriate DRM Returns as much as 35.41%; Review of the Accuracy of Filling out DRM for the exact Opname Warrant Form (SPO) 31.25%, the appropriate IGD Assessment Form 52.08%, the right Medical Resume Form 100%, and the proper Observation Form 66.67%; DRM Readability Review for Opname Warrant Form (SPO) which reads 100%, IGD Assessment Form that reads 77.08%, Medical Resume Form that reads 100%, and Observation Form that reads 72.92%; Drm Completeness Review for Screening Form found in 68.75% of documents, Triage Form found in 77.08% documents, Internal Transfer Form found on 89.58% of documents, Discharge Planning Form found on 81.25% of documents.For General Consent Forms, Inpatient Assessments, CPPT Forms, Observation Forms, and Information and Education Forms are found in all documents that are 100%. It is recommended that the existing SPO socialization prioritizes the accuracy of filling out medical records qualitatively, not limited to the completeness of the form only.